Virulence factors in Escherichia coli strains isolated from pigs in the Ribeirao Preto region, State of Sao Paulo, Brazil. - Carvalho, A. C.; Avila, F. A.; Schocken-Iturrino, R. P.; Quintana, J. L.; Albertini, P. E. (My University, 1991)
Three-hundred faecal swabs were obtained from pigs with diarrhoea in farms located in different areas of the Ribeirao Preto region in the State of Sao Paulo. One-hundred Escherichia coli strains were isolated and tested for production of thermolabile (TL) and thermostable (STRa and STb) enterotoxins, and for the presence of colonization factors F4, F5 and F6. The strains were also tested for sensitivity to 14 antibiotics and chemotherapeutic agents. Twenty-four Escherichia coli strains produced enterotoxin STb, 5 produced LT and 3 produced STa. In the mannose-resistant haemagglutination reaction, one strain reacted positively with sheep, chicken, horse and human red blood cells and another reacted positively with guinea pig, sheep, chicken, horse and human red cells. However, both strains were negative for colonization factors F4, F5 and F6 when submitted to the slide agglutination test. All Escherichia coli strains were resistant to at least one antibiotic, the highest percentages being obtained for resistance to penicillin, tetracycline and cephalotin. In addition to the importance of the virulence factors normally encountered in enterotoxigenic Escherichia coli strains from pigs, the present results show the possible existence of new colonization factors other than F4, F5 and F6 participating in E. coli-induced pigs colibacillosis in the Ribeirao Preto region.
Keywords: animal; animal disease; Brazil; diarrhea; Escherichia coli; feces; microbiology; pathogenicity; swine; swine disease; virulence; Animal; Diarrhea; Feces; Swine; Swine Diseases; Virulence